1994
DOI: 10.1001/archpsyc.1994.03950090064009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Early Onset of Male Antisocial Behavior From Preschool Behavior

Abstract: The behavioral activating system appears to be the major dimension underlying the propensity toward early onset of antisocial behavior, but both the behavioral inhibition system and the need for social rewards play important roles. The behavioral style (personality) that results from the interplay of these systems is clearly in place by the kindergarten year. Preventive efforts should target preschool children with at-risk behavior profiles. However, longitudinal-experimental studies with at least yearly asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
297
0
17

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(339 citation statements)
references
References 31 publications
25
297
0
17
Order By: Relevance
“…For example, Walker, Lahey, and Russo (1991) found that clinic-referred boys with conduct disorder and a comorbid anxiety disorder had fewer peer nominations of aggressive behavior, school suspensions, and police contacts than boys with conduct disorder alone. Similarly, anxiety, shyness, and behavioral inhibition have been associated with decreased delinquency (Tremblay, Pihl, Vitaro, & Dobkin, 1994). This research suggests that depressive and anxious symptoms moderate aggressive youths' risk for involvement in dangerous or illegal behaviors, which are known risk factors for community violence exposure (Centers & Weist, 1998;DuRant, Getts, Cadenhead, & Woods, 1995).…”
Section: Youth Behavior As a Risk Factor For Community Violence Exposurementioning
confidence: 98%
“…For example, Walker, Lahey, and Russo (1991) found that clinic-referred boys with conduct disorder and a comorbid anxiety disorder had fewer peer nominations of aggressive behavior, school suspensions, and police contacts than boys with conduct disorder alone. Similarly, anxiety, shyness, and behavioral inhibition have been associated with decreased delinquency (Tremblay, Pihl, Vitaro, & Dobkin, 1994). This research suggests that depressive and anxious symptoms moderate aggressive youths' risk for involvement in dangerous or illegal behaviors, which are known risk factors for community violence exposure (Centers & Weist, 1998;DuRant, Getts, Cadenhead, & Woods, 1995).…”
Section: Youth Behavior As a Risk Factor For Community Violence Exposurementioning
confidence: 98%
“…Several other studies have shown impressive correlations between preschool variables, such as impulsivity, irritability, and passivity, and personality patterns and behavior problems in adolescence and young adulthood ( Block, 1993 ;Caspi, Henry, McGee, Moffitt, & Silva, 1995 ;D. L. Newman, Caspi, Moffitt, & Silva, 1997 ;Tremblay, Pihl, Vitaro, & Dobkin, 1994 ). Mischel (1968Mischel ( , 1973 was once one of the most persistent critics of psychodynamic ideas, particularly the notion of consistency of personality over time and across situations.…”
Section: Continuity Over Time: a More Recent Interpretationmentioning
confidence: 99%
“…antisocial behaviour tend to be stable over time and predictive of a variety of adverse child outcomes including school failure (Loeber & Dishion, 1983;Olweus, 1979;Tremblay, Pihl, Vitaro, & Dobkin, 1994), especially in the context of family adversity (Campbell, Shaw, & Gilliom, 2000). Some early intervention programmes, for example, Early Head Start or home visitation programmes, target families whose children are at risk for developmental problems, including aggressive behaviour, while other programmes offer services to families whose young children are already exhibiting behaviour concerns.…”
mentioning
confidence: 99%